Productivity, energy use efficiency, economics and CO2 emission from integrated fish-duck farming in floodplain wetland ecosystems of eastern India - Ravi Kumar; M. Monobrullah; B. P. Bhatt; A. Raizada; A. R. Sen; S. K. Samal; Manoj Kumar (Indian Journal of Fisheries, 2023)
The study aims to assess productivity, economics, energy use efficiency and CO2e emissionfrom integrated fish-duck farming system (IFDF system) in floodplains of the eastern India.A total of six fish ponds were constructed and developed as IFDF system under floodplainsin which fingerlings were stocked @4000 acre-1 and integrated with 150 numbers of KhakiCampbell ducks. Average growth rate of fishes ranged from 27 g month-1 of mrigal to 31.7 gmonth-1 of grass carp and average body weight ranged from 465.2 g of mrigal to 823.2 gof grass carp. The fish equivalent yield was obtained as 3.06 t acre-1 year-1. The total energyinput, output and energy use efficiency ratio estimated were 111.8 GJ and 21.2 GJ and 0.19,respectively. Net income earned was ₹234393 acre-1 year-1 and BC ratio estimated was 1.91.Further, 0.56 kg CO2e was emitted to produce 1.0 kg of fish equivalent, which was muchlower than that of the production of rice, mutton and milk.Keywords:CO2e emission, Economics, Energy, Fish-duckfarming, Floodplain, Productivity